Differences in dopaminergic modulation to motor cortical plasticity between Parkinson's disease and multiple system atrophy. - Shoji Kawashima; Yoshino Ueki; Tatsuya Mima; Hidenao Fukuyama; Kosei Ojika; Noriyuki Matsukawa (PLoS ONE, 2013)
Dopamine modulates the synaptic plasticity in the primary motor cortex (M1). To evaluate whether the functioning of the cortico-striatal circuit is necessary for this modulation, we applied a paired associative stimulation (PAS) protocol that comprised an electric stimulus to the right median nerve at the wrist and subsequent transcranial magnetic stimulation of the left M1, to 10 patients with Parkinson's disease (PD) and 10 with multiple system atrophy of the parkinsonian type (MSA-P) with and without dopamine replacement therapy (-on/off). To investigate the M1 function, motor-evoked potentials (MEPs) were measured before and after the PAS. In both patient groups without medication, the PAS protocol failed to increase the averaged amplitude of MEPs. The dopamine replacement therapy in PD, but not in MSA-P effectively restored the PAS-induced MEP increase. This suggests that not the existence of dopamine itself but the activation of cortico-striatal circuit might play an important role for cortical plasticity in the human M1.